Nationwide improvement in outcomes of emergency admission for ulcerative colitis in England, 2005‐2013. Issue 2 (28th May 2019) - Shawihdi, Mustafa; Dodd, Susanna; Kallis, Constantinos; Dixon, Pete; Grainger, Ruth; Bloom, Stuart; Cummings, Fraser; Pearson, Mike; Bodger, Keith
Summary: Background: The UK IBD Audit Programme reported improved inpatient care processes for ulcerative colitis (UC) between 2005 and 2013. There are no independent data describing national or institutional trends in patient outcomes over this period. Aim: To assess the association between the outcome of emergency admission for UC and year of treatment. Methods: Retrospective analysis of hospital administrative data, focused on all emergency admissions to English public hospitals with a discharge diagnosis of UC. We extracted case mix factors (age, sex, co‐morbidity, emergency bed days in last year, deprivation status), outcomes of index admission (death and first surgery), 30‐day emergency readmissions (all‐cause, and selected causes) and outcome of readmission. Results: There were 765 deaths and 3837 unplanned first operations in 44 882 emergency admissions, with 5311 emergency readmissions (with a further 171 deaths and 517 first operations). Case mix adjusted odds of death for any given year were 9% lower (OR 0.91, 95% CI: 0.89‐0.94), and that for emergency surgery 3% lower (OR 0.97, 95% CI: 0.95‐0.98) than the preceding year. Results were robust to sensitivity analysis (admissions lasting ≥4 days). There was no reduction in odds for all‐cause readmission, but rates for venous thromboembolism declined significantly. Analysis of institutional‐level metrics across 136 providers showed a stepwise reduction in outliers for mortality and unplanned surgery. Conclusions: Risk of death and unplanned surgery for UC patients admitted as emergencies declined consistently, as did unexplained variation between hospitals. Risk of readmission was unchanged (over 1 in 10). Multiple factors are likely to explain these nationwide trends.